PENGUJIAN KUALITAS WEBSITE DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DUKCAPIL) KOTA DENPASAR BALI MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - I Gede Sugita Aryandana; Leni Anggraini Susanti; Putu Eka Suardana; Putu Virgananta Nugraha (LPPM Universitas Dhyana Pura, 2025)
Websites play a crucial role in providing efficient digital information and services across various sectors, including the government sector. In this sector, an optimal website is a key factor in enhancing public service efficiency, particularly in facilitating public administration and ensuring that population services are conducted more effectively and responsively to meet society's needs. The Civil Registry and Population Office (DUKCAPIL) of Denpasar City is a public service agency that operates an official website at taringdukcapil.denpasarkota.go.id. This website serves as a platform for providing information on public administration and population services. However, its information delivery is still suboptimal, with issues such as user-unfriendly navigation, infrequent information updates, and difficult access to older news content. As a result, users struggle to obtain the necessary information. To assess the quality of the DUKCAPIL website, quality evaluation was conducted using System Usability Scale (SUS) method, which measures usability based on five key dimensions: Easy to Use, User Competence, Efficiency, System Reliability, and Design. The evaluation was carried out in Denpasar City using questionnaires and a random sampling method. Based on the assessment, the DUKCAPIL Denpasar City website was classified as grade F with a